MORPHOMETRIC AND MOLT OF THE CRESCENT-CHESTED BABBLER (STACHYRIS MELANOTHORAX) IN CISARUA FOREST, WEST JAVA - Fransisca Noni Tirtaningtyas; Yeni Aryati Mulyani; Dewi Malia Prawiradilaga; Joseph Adiguna Hutabarat; Iis Sabahudin (BRIN Publishing (Penerbit BRIN), 2016)
Crescent-chested Babbler is endemic to the island of Java and Bali, Indonesia and protected by the Indonesian Government Regulation No. 7/ 1999. Its population is suspected to be declining due to ongoing habitat destruction and fragmentation. Information on its eco-biology is very poorly known. There is a need to obtain the information in order to conserve this species and its habitat. Morphometric and molt stages were recorded from 23 individuals captured by mist-nets between February and April 2016. There were variations in morphometric measurement in weight, head bill length, wing length and tail length in Cisarua Forest habitat, but no significant difference was found (F2.19 = 0.822, P> 0.05) in body weight among the three different habitats. This habitat has sufficient resource for Crescent-crested Babbler for molt activity during the study.